Traumatic Pediatric Tracheal Rupture After Blunt Force Sporting Injury: Case Report and Review of the Literature. (August 2022) - Taylor, Alon; Menon, Seema; Grant, Peter; Currie, Bruce; Soma, Marlene
Objective: This paper presents the case of a traumatic tracheal rupture in a pediatric patient. The body of literature of the clinical features, evaluation, and management of this uncommon presentation is discussed. Case: A 13-year-old boy sustained an intrathoracic tracheal rupture whilst playing Australian Rules football. He developed hallmark clinical features of air extravasation and was intubated prior to transfer to a tertiary pediatric center for further management. After a short trial of conservative management, his respiratory status deteriorated and he was taken to the operating theater for open surgical repair of the defect. Conclusion: Traumatic rupture of the trachea is a rare injury in children. This case demonstrates the dynamic nature of this serious injury and the need for multidisciplinary care in achieving the optimal outcome.